Identifying fibroblast growth factor receptor genetic alterations using RNA‐based assays in patients with metastatic or locally advanced, surgically unresectable, urothelial carcinoma who may benefit from erdafitinib treatment - Songbai Wang; Mike Burgess; Christopher Major; Alistair English; Maranna Sweeney; Arndt Hartmann (Wiley, 2020)
Abstract Erdafitinib, a pan‐fibroblast growth factor receptor (FGFR) inhibitor received accelerated approval from the US Food and Drug Administration (FDA) for locally advanced or metastatic urothelial carcinoma (mUC) in adult patients with specific FGFR3/2 genetic alterations who progressed during or after ≥1 line of prior platinum‐containing chemotherapy (PCC), including within 12 months of neoadjuvant or adjuvant PCC. Concordance between the clinical trial assay (CTA) used in a phase 2 study and QIAGEN's therascreen® FGFR kit (a two‐step, multiplex, real‐time, RT‐PCR assay), the FDA‐approved companion diagnostic (CDx) with erdafitinib, was evaluated in this bridging study. Study samples included 100 CTA‐confirmed FGFR‐positive samples from 100 erdafitinib‐treated mUC patients, plus 200 CTA‐confirmed FGFR‐negative samples from the phase 2 study. The primary objective was met if the lower bound of 95% CI of objective response rate (ORR) in CDx‐confirmed patients with FGFR alterations was >25%. Demographics were similar between the bridging study and CTA‐screened patients. In total, 292 of 300 samples (97.3%) with valid CDx results showed high analytical concordance versus CTA (percent agreement [95% CI]: positive percent agreement, 87.2 [79.0; 92.5]; negative percent agreement, 97.0 [93.5; 98.6]; overall percent agreement, 93.8 [90.5; 96.1]). Investigator‐assessed ORR in the 81 CDx‐identified, erdafitinib‐treated patients who tested positive for both assays was 45.7% (95% CI: 35.3%; 56.5%) versus 40.4% (95% CI: 30.7%; 50.1%) for CTA and met the criteria for primary objective. High ORR and clinical concordance to CTA suggest that QIAGEN's CDx can reliably select mUC patients who would potentially benefit from erdafitinib treatment.